Targeted Pregnancy and Human Immunodeficiency Virus Prevention Risk-Reduction Counseling for Young Women: Lessons Learned from Biomedical Prevention Trials. (26th June 2018) - Ramjee, Gita; Dassaye, Reshmi; Reddy, Tarylee; Wand, Handan
Abstract : Women enrolled in HIV prevention trials in KwaZulu-Natal, South Africa between 2002 and 2012 have overlapping risk factors for pregnancy and HIV incidence. This emphasizes an urgent need for appropriate, targeted, individual-centred counseling for women participating in HIV prevention trials. Abstract: Background: Women enrolled in human immunodeficiency virus (HIV) prevention efficacy trials receive counseling on prevention of HIV, sexually transmitted infections (STIs), and pregnancy during every visit. Incident pregnancy has an impact on efficacy outcomes. Incidence rates of pregnancy and HIV/STIs among women who became pregnant and associated risk factors were assessed. Methods: Data from 9165 women participating in HIV prevention trials in KwaZulu-Natal, South Africa from 2002–2012 were combined. Demographic and behavioral predictors of incidence pregnancy and incidence HIV and STIs were determined using Cox regression models. Results: Overall pregnancy incidence was 9.6 per 100 person-year (py) (95% confidence interval [Cl], 9.1–10.3). Human immunodeficiency virus incidence among pregnant women was 5.93 per 100 py (95% Cl, 4.73–7.44). Incidence of STIs among pregnant women for Chlamydia trachomatis, Trichomonas vaginalis, Neisseria gonorrhoeae, and Treponema pallidum (syphilis) were 10.87, 7.42, 3.92, and 1.43 per 100 py, respectively. In the adjusted analyses, we observed overlapping risk factors for HIV acquisition during pregnancy, ie, young age, not married/not cohabitating, and low parity. The risk of pregnancy and HIV acquisition is more than 3 times higher among young women (<20 years of age). Conclusions: We identified overlapping risk factors for pregnancy and HIV incidence, suggesting an urgent need for appropriate, targeted, individual-centred counseling for women participating in HIV prevention trials.